Proceedings of the Symposium on Non-Photorealistic Animation and Rendering 2017
DOI: 10.1145/3092919.3092924
|View full text |Cite
|
Sign up to set email alerts
|

Depth-aware neural style transfer

Abstract: style loss and content loss. However, such pre-trained networks are originally designed for object recognition, and hence the high-level features o en focus on the primary target and neglect other details. As a result, when input images contain multiple objects potentially at di erent depths, the resulting images are o en unsatisfactory because image layout is destroyed and the boundary between the foreground and background as well as di erent objects becomes obscured. We observe that the depth map e ectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…Jiang'17 [89] Fashion Chen'18 [72] 3D 2D Johnson'16 [47] Ulyanov'16 [48] Ulyanov'17 [50] Li'16 [52] Liu'17 [63] Depth Wang'17 [62] Jing'18 [61] Stroke Size Improvement Image Video Huang'17 [78] Gupta'17 [79] Chen'17 [80] Lu'17 [70] Semantic Non-Photorealistic Zhang'17 [87] Photorealistic Azadi'18 [83] Character Figure 2: A taxonomy of NST techniques. Our proposed NST taxonomy extends the IB-AR taxonomy proposed by Kyprianidis et al [14].…”
Section: Per-style-per-model Neural Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jiang'17 [89] Fashion Chen'18 [72] 3D 2D Johnson'16 [47] Ulyanov'16 [48] Ulyanov'17 [50] Li'16 [52] Liu'17 [63] Depth Wang'17 [62] Jing'18 [61] Stroke Size Improvement Image Video Huang'17 [78] Gupta'17 [79] Chen'17 [80] Lu'17 [70] Semantic Non-Photorealistic Zhang'17 [87] Photorealistic Azadi'18 [83] Character Figure 2: A taxonomy of NST techniques. Our proposed NST taxonomy extends the IB-AR taxonomy proposed by Kyprianidis et al [14].…”
Section: Per-style-per-model Neural Methodsmentioning
confidence: 99%
“…Another limitation of current NST algorithms is that they do not consider the depth information contained in the image. To address this limitation, the depth preserving NST algorithm [63] is proposed. Their approach is to add a depth loss function based on [47] to measure the depth difference between the content image and the stylised image.…”
Section: Improvements and Extensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary version of this paper has been published in NPAR 2017 [30]. [20], tend to scatter the textures over the stylized outputs, and ignore the structure information in an image.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous works have demonstrated that preserving structures can produce attractive artistic results [13], [36], [46]. Considering that a depth map can effectively capture the global structure of the scene [16], [40], the early version of this paper [30] integrates depth as an additional representation to preserve overall image layout during style transfer. Which image stylization seems best to you?…”
Section: Introductionmentioning
confidence: 99%